Islamic Perception of Shopping Mall Through the Dimension of Facility Management - Yang Haziqah Musa; Adibah Yusuf; Nangkula Utaberta; Ismar M. S. Usman; Mahendra Wardhana (Department of Architecture, Faculty of Science and Technology, UIN Maliki Malang, 2023)
A shopping mall refers to a structure with several retail establishments managed as a single property that offers various products and services. It has become essential to the functioning of contemporary society, particularly for residents of urban and suburban areas. However, concerns or issues regarding facilities and services in shopping malls continue to surface even today. Past studies have suggested that facility management is a best practice for overcoming management and operation issues. It also aligns with the Islamic principle as it is beneficial knowledge relevant to the modern management approach. Therefore, this paper seeks to comprehend the potential facility management approach to shopping mall management. The main objective of this study is to emphasize the importance of facility management in shopping malls by evaluating consumer satisfaction. A survey is conducted with a total sample of 200 respondents based on three facility management maintenance characteristics: functional, technical, and image. One of the reputable shopping malls in Johor Bahru is selected for this study because it attracts numerous visitors from throughout Johor Bahru. The results show that most of the visitors are pleased and satisfied with all three aspects from the dimension of facility management.